Concentrações plasmáticas de mepivacaína em pacientes submetidos à cirurgia de terceiros molares - Maia, Raimundo Nonato (2008)
Surgical removal of the third molars in clinical regime making use of local anesthetics plays a great role in the everyday practice of odontology. These drugs are safe when used in the proper way, but they can lead to undesirable outcomes when used in the wrong quantities or concentrations. Based on the knowledge of such principle and on surgical clinical practice, where levels of anesthetic concentration in the blood can reach near-toxic levels, a study measuring the systemic concentration of local anesthetic was made by collecting and analyzing, in equipment of High-performance liquid chromatography (HPLC), blood samples of patients who were submitted to local anesthesia with mepivacaine 2% and adrenaline 1:100000 for the removal of the third molars. The study was relevant because mepivacaine is frequently used in ambulatory surgeries of third molars, making it important to investigate the behavior of plasmatic levels and their possible toxic manifestations. The sample consisted of twenty-six patients of both sexes, subdivided in two groups according to the number of third molars removed: one group had two removed in a single session, the other group had four. Monitoring was done using pulse oxymetre, regular measuring of blood pressure, heart rate, and electrocardiogram in radioscopic, according to the minimum recommendations of the American Association of Oral and Maxillofacial Surgeons (D´ERAMO et al, 2003). In the interval of 120 minutes there were collected 10 samples of 4 mL after the injection of local anesthetic, and the quantitative analysis of the plasmatic concentrations of mepivacaine was done in HPLC. The plasmatic levels of mepivacaína in both groups were growing and significant amongst themselves in all the respective intervals of collections of the sanguine samples. After the results were obtained, the values at each corresponding moment for both groups were compared, showing that the averages of the systolic and diastolic pressure of all of the intervals were not significant when compared with the values obtained in the preoperative consultation. According to the results this study it was possible to conclude that the surgery of third molars under local anesthesia, with mepivacaine 2% and adrenaline 1:100000, when respecting the safety margins recommended by the manufacturer, is a safe procedure and that there are no clinical systemic differences to the healthy patient when doses between 108mg (5,4mL) and 216mg (10,8mL) are used.